Shifting ideas about ancestors in the construction of identities : an intercultural theological evaluation of Korean witnesses in South Africa - Kwon, Hyo-Sang (Stellenbosch : Stellenbosch University, 2012)
Thesis (DTh)--Stellenbosch University, 2008.